Multi-valued logic arbiter PUF designs based on CNTFETs. (September 2022) - Momeni, Hossein; Ghazizadeh, Amir; Sharifi, Fazel
Abstract: Arbiter physical unclonable functions (APUFs) are integrated circuits (ICs) capable of storing secret keys spontaneously, which makes them a great fit for electronic device authentication and key generation applications. In this work, we propose two novel designs of multi-valued logic (MVL) APUFs using carbon nanotube field effect transistors (CNTFETs). Using MVL will enhance the APUF security by increasing the size of challenge-response pairs. The proposed designs are investigated under the 32nm CNTFET standard model library using HSPICE simulations. On average, the randomness in the ternary and the quaternary APUF responses are 32.75% and 24.47% in the worst case respectively, which are near the ideal randomness of 33.33% and 25%. Also, we analyzed the reliability of the proposed APUFs in different temperatures and supply voltages. Additionally, we implemented and analyzed the proposed designs using the 14nm CNTFET standard model library to ensure that our designs maintain stability.